Reformado de metano en seco utilizando perovskitas La1-XAXNiO3 y LaNi1-XBXO3 (A: Ce ó Pr y B: Co ó Mg) como precursores del catalizador (2010)
ABSTRACT: Perovskite-type LaNiO3 was synthesized by four different methods: autocombustion, sol-gel, calcination of nitrate and freeze-drying. The catalyst that presented the highest activity in terms of conversion of CH4 and CO2 to H2/CO was obtained from perovskites synthesized by the autocombustion method. The Co-containing catalysts showed less activity than those with only Ni. This decrease in activity was attributed to the formation of Co-Ni alloy. The Mg-substituted catalysts showed a decrease in carbonaceous deposits due probably to increased basicity of the catalysts. The greatest resistance to the accumulation of carbonaceous deposits was observed on the catalysts containing Ce and Pr, which is attributed to the redox properties of oxides (PrYOX and CeYOX) which facilitate the gasification of carbonaceous deposits formed during the reaction.